The Granite Coast murders - Bannalec, Jean-Luc, 1966- (A Brittany mystery, 2021)
"In The Granite Coast Murders, the sixth installment of Jean-Luc Bannalec's bestselling mystery series, Commissaire Dupin returns to investigate a murder at a gorgeous Brittany beach resort. Inspector Dupin and Claire are on a two-week vacation, but while Claire seems to enjoy the quiet of the beach, Commissaire Dupin takes every opportunity to leave the beach towel. The fabulous dinners on the hotel patio and the rumors about a stolen statue of a saint are the few interesting moments of his days on vacation. But then a tourist vanishes without trace and there's an attack on a deputy to the local assembly, who is involved in confrontations with local farmers. Shortly after that, the Britanny beach resort is shocked by the discovery of a corpse. Dupin clandestinely begins to investigate with the help of the local villagers, something he must keep a secret from Claire and his colleagues in Concarneau. Between bewitched valleys and beautiful beaches, an unfathomable case develops"--